Impact of Land Transport Combustion on air quality and public health in urban areas. A Review - Patiño-Sánchez, Angie Catherine; Patiño-Silva, Oscar Francisco (Universidad Antonio Nariño, 2021)
Land transportation is a necessity today, whose operation is generated mainly by the use of fossil fuels, which through incomplete combustion in motor vehicles generate the energy necessary for their movement, as well as the emission of carbon monoxide, carbon dioxide, nitrogen oxides, sulfur oxides and volatile organic compounds, which in contact with humans are considered the main causes of respiratory, carcinogenic and blood diseases. In this sense, in this article a compilation of the investigations carried out at a global level is made, which will determine the relationship between the combustion associated with the operation of land transport and the levels of pollution that check air quality and public health. According to global research, it is found that particulate matter (PST, PM10 and PM2.5) is the main pollutant that is related to the influence of land transport on public health.